The wall is dead, short live graffiti and street art! Graffiti, street art and the Berlin Wall's heritage - Pinto, Sofia (2021)
This article addresses some of the challenges faced by heritagization related to graffiti and street art, namely the changes in context and temporality that this process entails. In order to discuss these issues, I will frame the Berlin Wall as a paradigmatic case that presents a trajectory in time: I will follow the transition of the Wall from a deadly frontier to an obsolete structure and, finally, to a historic monument. I will argue that graffiti and street art are context-specific, and deeply affected by the symbolism and/or functions of the surface on which they are inscribed. Moreover, I will recognize graffiti and street art as practices situated in between tangible and intangible heritage. Particularly with the Berlin Wall, and in regard to the preservation of memory and heritage, I will suggest that graffiti and street art do not always enter the institutional circuit, especially when illegal and anonymous.